Assessment of the clinical and nutritional profile of adolescents with primary dysmenorrhea - Lais Buard Pontes Strobel Fakri; Aline de Piano Ganen; Guido de Paula Colares Neto (O Mundo da Saúde, 2024)
Pelvic pain in adolescents, especially during the menstrual period, is often underestimated as a health problem and significantly impacts quality of life. The objective was to evaluate the clinical and nutritional profile of adolescents with dysmenorrhea. 40 adolescents were selected, aged between 11 and 19 years old, treated at a teaching clinic in São Paulo, as well as using the snowball technique. Pelvic pain was assessed using a validated pain scale questionnaire and food consumption was assessed using a 24-hour dietary recall and Food Frequency Questionnaire. All participants had adequate height for their age and 72.5% were eutrophic. Thirty-five patients (87.5%) had moderate to severe pain, while five (12.5%) had mild or no pain. Practicing physical activity was less common among the group with moderate to severe pain (34.3%). There was no significant difference in the length of menstrual cycles between the groups. Lower calcium intake was observed in the group with more intense menstrual pain. Furthermore, there was a lower consumption of 'fresh' and "processed" foods in the group with moderate to severe pain during lunch and dinner meals, respectively. A negative correlation was identified between calcium and folate consumption and the duration of pain in days. The sample studied suggests that a balanced diet, rich in calcium, folate and natural foods, may be important in the management of dysmenorrhea. However, more research is needed to fully understand this relationship and develop effective interventions to treat this common condition among adolescents.